Metastatic papillary thyroid carcinoma with internal jugular vein tumor thrombus - A case report and review of the literature - Adnan, Zaina; Sabo, Edmond; Kassem, Sameer (Frontiers in Endocrinology, 2025)
Papillary thyroid carcinoma (PTC) is the most common malignancy of the thyroid gland, typically associated with an indolent course and favourable prognosis. However, although rare, PTC can demonstrate aggressive behaviour, including vascular invasion with extension into major vessels. Intraluminal tumor thrombus involving the great veins, such as the internal jugular vein (IJV), is an uncommon but significant complication. We present the case of a 56-year-old male who was referred to our clinic for evaluation of a right-sided anterior neck mass. Neck ultrasonography revealed a 5.5 x 6.5 cm heterogeneous mass within the right thyroid lobe and a suspected intraluminal thrombus in the right internal jugular vein. Fine-needle aspiration biopsy under ultrasound guidance confirmed the diagnosis of papillary thyroid carcinoma. Subsequent preoperative contrast-enhanced computed tomography (CT) of the neck confirmed the presence of an intraluminal tumours thrombus extending into the right IJV. The patient underwent total thyroidectomy, right modified radical neck dissection, and resection of the involved segment of the IJV. Postoperatively, the patient received radioactive iodine (I-131) ablation therapy. At the one-year follow-up, imaging studies indicated a recurrence of the disease. A review of the literature focusing on vascular involvement in PTC and diagnostic methods for tumours thrombus reveals that, while rare, intraluminal tumor thrombus should be considered in patients with PTC, especially when there is evidence of vascular invasion. Early and accurate preoperative diagnosis using Doppler ultrasonography and/or contrast-enhanced CT is critical for optimal surgical planning and improved prognosis. Given the potential for recurrence, vigilant long-term follow-up is recommended.